Luminescent Porous Silicon Filled with Nanoscopic Magnetic Structures – Assessment of the Optical and Magnetic Properties. (8th September 2020) - Granitzer, Petra; Rumpf, Klemens; Reissner, Michael; Michor, Herwig
Abstract : Luminescent porous silicon which is denoted as microporous silicon (LPSi) offers a structure size of a few nanometers. The pores are arranged in a branched network-like morphology. These structures are filled with magnetic metals resulting in a composite system with specific optical and magnetic properties. In this work Ni and Co, respectively are used. The luminescence is observed in the red-orange region due to the small structure size. The photoluminescence spectra of initial LPSi offer a peak around 620 nm, which is blue-shifted after Ni-filling with increasing deposition time and the intensity of the luminescence is increased. In the case of Co deposition the spectrum is adequate but with increasing metal filling the luminescence intensity decreases. Magnetic field dependent measurements performed for easy and hard axis magnetization show a high magnetic anisotropy between these two magnetization directions, even more pronounced in the case of Co. The magnetic response of the samples is related to the interconnected pores and differs significantly to mesoporous silicon filled with magnetic nanostructures.